Planar cavity-backed antenna prototype by groove waveguide technique (2020)
A new Cavity-Backed Antenna prototype compatible with planar technology is presented is this paper. The topology and circuit design are presented. The antenna is completely manufactured in hard-aluminum. The Cavity-Backed Antenna prototype is designed by using Groove waveguide technique. The new antenna prototype consists of a slotted cavity fed by a microstrip line. Two prototypes were designed and manufactured. The first prototype was designed with three metal walls and the second prototype has been manufactured with two metal walls. In this new antenna prototype the specific slot patterns on the cavity back face such as edge slots and meandered are combined. An example with a minimum 10 dB return loss bandwidth of 1.3%, 6.5 dBi gain, and 21.2 dB front to back ratio has been presented. The new Cavity-Backed Antenna prototype can be used in hyperthermia treatment.